Economic Growth, Human Capital, Public Investment, and Poverty in Underdeveloped Regions in Indonesia - Wau, Taosige (Universitas Muhammadiyah Yogyakarta, 2022)
Poverty is a worldwide issue since its effects are widespread. In Indonesia, most pockets of poverty are found in rural or underdeveloped areas. This research is essential as a reference for addressing the issue of poverty in Indonesia's undeveloped regions, as few studies have analyzed the causes of poverty in underdeveloped regions. This study analyses the impact of economic growth, human capital, and public investment on the alleviation of poverty in Indonesia’s undeveloped regions. This study employs panel data from 62 underprivileged regions in Indonesia according to Presidential Decree No. 63 of 2020 with an observation period of 2010-2020. The analytical method used is the ECM panel model. The unit root test indicates that the research data is steady and cointegrated at the first level of differentiation. This study demonstrates that economic growth does not have a substantial influence on poverty levels in underdeveloped areas of Indonesia, although human capital and public investment do, both in the short and long term. Human capital contributes more to reducing poverty in disadvantaged areas, but state investment increases the number of poor in Indonesia's underdeveloped regions.